PENGARUH KETIDAKPUASAN KONSUMEN DAN KEBUTUHAN MENCARI VARIASI TERHADAP KEPUTUSAN PERPINDAHAN MEREK HANDPHONE ANDROID DARI SAMSUNG KE OPPO (STUDI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS KHAIRUN TERNATE) - Lamani, Nurhidayanti N; Hidayanti, Ida; Hi. Yusuf, Ibnu Sina (Jurnal Manajemen Sinergi, 2020)
Objective: The purpose of this study was to determine the effect of Consumer dissatisfaction (the need to find variations and the transfer of Android mobile brands from Samsung to OPPO) through Smartphone users of the Khairun ternate University of Economics and Business students, the number of research samples was 100 economic sample students in this study using Purposive sampling and snowboil sampling. Methodology: The analytical method used is multiple linear regression analysis. Finding: H1 H2, and H3 accepted at the 5% confidence level. Conclusion: The results showed that (1) Partial dissatisfaction had a significant effect on brand displacement in Economics Students of Khairun University, Ternate, (2) Needs to find variations had a positive and significant effect on brand displacement on Economics Students of Khairun University of Ternate, and (3) Consumer Dissatisfaction, Needs Looking for Variations Simultaneously has a significant positive effect on the transfer of Economics Students brand of the Khairun University, Ternate